SYNERGY OF RELIGIOUS FIGURES WITH THE INDONESIAN ARMED FORCES AND THE REPUBLIC OF INDONESIA POLICE IN OVERCOMING RADICALISM MOVEMENTS TO SUPPORT STATE DEFENSE IN EAST JAVA - Rini Windiyawati (The Republic of Indonesia Defense University, 2021)
The synergy between religious figures, community leaders, the Indonesian Armed Forces (TNI), and the Republic of Indonesia Police (POLRI) is urgently needed for the government is facing radicalism movements in Indonesia. Entering the reformation era, radical ideologies have the possibility more to threaten national security. This study aims to describe the synergy between religious figures, the Indonesian Armed Forces, and the Republic of Indonesia Police to ward off radical movements in East Java. Radicalism is closely related to terrorism, both of which are acts of violence or threats to people's lives. Therefore, it is necessary to have synergy from several parties. The research approach in this research uses qualitative phenomenological research. According to the results of the study, it shows that 1) the factors that cause the rise of radicalism movements in East Java are the greatest lack of education and poverty and 2) the synergy between religious figures, Indonesian Armed Forces, and the Republic of Indonesia Police has been running quite well. It can be seen from good cooperation in carrying out duties and responsibilities in maintaining national integrity, especially in preventing radicalism movements by the religious figure by carrying out various activity agendas as socialization in preventing radicalism movements in East Java.